Student Placements in Occupational Health Services: nursing and physiotherapy. (31st December 2022) - Brown, Clare; McDowall, Kiera; Murphy, Elizabeth; Bell, Josh
Abstract : This article outlines the practical considerations of establishing student placements in occupational health services. The placements have enhanced recruitment to both the occupational health service and the wider NHS environment. It is anticipated that the ongoing programme will offer practical placements and increase the wider understanding of the value of occupational health in the working-age population.